Emotional discourse and symbolic contestation in Indonesia's digital public sphere: an ethnographic content analysis of online reactions from YouTube comments on LPG subsidy regulatory adjustment news - Nasrullah, Rulli; Murodi; Suhaimi; Musyarrofah, Umi; Khoiriyah, Nunung; Saraka, Muhammad Yahya (Frontiers in Communication, 2026)
IntroductionThe regulatory adjustment to Indonesia's subsidized 3-kilogram LPG distribution in February 2025 triggered widespread public unrest and rapidly became a national controversy. The temporary suspension of retail sales produced acute shortages for households and small businesses, leading to significant media amplification and extensive debate across digital platforms. As YouTube increasingly functions as a participatory space for public expression, understanding emotional discourse and symbolic contestation in its comment sections is essential for analyzing how digital publics articulate grievances and influence policy communication.MethodsThis study employed Ethnographic Content Analysis (ECA) to examine 426 YouTube comments posted between February 5 and March 1, 2025, responding to the MetroTV news clip covering the LPG subsidy controversy. Comments—including both primary comments and replies—were treated as independent units of analysis. Sentiments were categorized using a six-type framework adapted from Amarasekara and Grant (2019): appearance, sexual/sexist, hostile, positive, critiques/negative, and general/neutral. Two coders independently applied the coding scheme, achieving near-perfect reliability (Krippendorff's Alpha = 0.993). The ethnographic approach enabled analysis not only of textual meaning but also of communicative markers such as phrasing, capitalization, emojis, and rhetorical style.ResultsFindings show that negative and critical comments dominated the discourse (197 comments), followed by hostile sentiment (87 comments). These comments frequently expressed frustration, socio-economic grievances, and delegitimization of authority. Positive sentiment (55 comments) was directed not at government officials but at a citizen who confronted the minister, indicating the emergence of symbolic figures representing collective discontent. Appearance-based (17 comments) and sexual/sexist (1 comment) sentiments, though fewer, illustrated the degradation of discourse into ad hominem attacks. Neutral comments (69 comments) reflected factual observations, rhetorical questioning, or conversational engagement. Overall, the comment section functioned as an arena for emotional release, symbolic contestation, and affective communication.DiscussionThe study demonstrates that YouTube comment sections operate as affective extensions of the digital public sphere, where emotional intensity and symbolic representation shape civic engagement. Emotional discourse—including sarcasm, humor, ridicule, and direct criticism—served as a mechanism of civic accountability and revealed public dissatisfaction with governance and policy implementation. The prominence of symbolic figures, such as the protesting citizen, underscores how digital publics mobilize emotional narratives to articulate social frustration. These findings extend theoretical understandings of digital participation, highlighting the role of affect, symbolic activism, and ethnographic insight in interpreting public discourse on social media platforms.